Pkm Appropriate Technology Training for Making Granule Organic Fertilizers in Gogodeso and Munggalan Villages - Irawan, Dani; Bisono, Rahayu Mekar (Jurnal ABDINUS : Jurnal Pengabdian Nusantara, 2019)
One of the activities of the "Makmur Jaya Farmers" group in Gogodeso village and the "Ngudi Makmur Farmers" group in Munggalan village is currently making simple organic fertilizers with raw materials derived from cow manure. however, there are still obstacles that are felt by the local community, namely the inefficiency in the manufacturing process. The problem of partners in community service is the limited technology for managing organic fertilizer. Mitra needs to empower technology in managing organic fertilizer. The processing already exists and produces powder fertilizers that have economic value. But the processing is still very traditional, causing new problems in the amount of fertilizer spread because of the powder-based fertilizer. Therefore, this needs to be touched by the development of Appropriate Technology to produce granular organic fertilizer with good and correct processing as an economic source to increase family income as community empowerment. as well as marketing the products produced by these Community Service Results partners, it can be concluded that this training was quite successful where the training participants were very enthusiastic in the training activities, it was also because each teacher had never received socialization from the government / agricultural services related to the use of technology appropriate for processing fertilizers into processed products that are ready to sell / value as well as increasing the capacity and income of activity partners with the transfer of recycling technology for manure. Suggestions, in order to improve technology transfer to the community micro business groups, should be activities such as the community service program PKM need to be promoted so that the community's ability to increase which at the same time will improve the community welfare of farmer groups.